THE BUDDHA’S TEACHING ON TILAKKHAṆA: A BUDDHIST DECONSTRUCTION OF SOUL THEORY IN INDIAN PHILOSOPHY - Kustiani; Medhacitto, Tri Saputra (Jurnal Agama Buddha dan Ilmu Pengetahuan, 2024)
This research aims to examine the Buddha’s teaching on Tilakkhaṇa and present the critical analysis on how the Tilakkhaṇa teaching can be used to reject the soul theory. By using the qualitative research methodology, carried out with library approach, this research presents comprehensive explanation on the non-soul theory (anatta) presented by the Buddha in order to counter the soul theory. Tilakkhaṇa is the philosophical teaching to prove that soul theory is ungrounded. The three characteristics of existence such as impermanence (aniccā), suffering (dukkha) and non-self (anattā) are the truth of existence rejecting the soul theory. It is because all conditioned things are impermanent, therefore they are fraught by suffering (yad aniccaṃ taṃ dukkhaṃ). Because they are impermanent and suffering, therefore they are to be seen as non-self. Whatever suffering, it is also non-self (yaṃ dukkhaṃ tadanattā). By utilizing the content analysis method, this research contributes an insight on how Tilakkhaṇa teaching is applied to reject the soul theory.